Apical PtdIns(4, 5)P2 is required for ciliogenesis and suppression of polycystic kidney disease. Issue 2 (15th October 2018) - Xu, Wenyan; Jin, Miaomiao; Huang, Weilai; Wang, Hong; Hu, Ruikun; Li, Jingyu; Cao, Ying
ABSTRACT: Cilia are hair‐like structures that function like antennae to detect chemical and mechanical signals in the environment. Recently, phosphoinositides were shown to play an important role in cilia assembly and disassembly. However, the precise molecular and cellular mechanisms underlying this process remain unknown. Here, we report that suppression of apical phosphatidylinositol 4, 5‐ bis phosphate [PtdIns(4, 5)P2 ], by overexpressing apically targeted PtdIns(4, 5)P2 phosphatase or by knocking down type I phosphatidylinositol 4‐phosphate 5‐kinase (Pip5k1), leads to ciliogenesis defects and polycystic kidney disease (PKD) in zebrafish embryos that phenocopied inpp5e mutant, a Joubert syndrome model. We further demonstrate that decreased expression of apical PtdIns(4, 5)P2 disrupted apical ezrin recruitment, F‐actin organization, and basal body docking. Moreover, the ciliogenesis and polycystic kidney defects in PtdIns(4, 5)P2 ‐depleted embryos can be rescued by overexpression of ezrin. Finally, Pip5k1a overexpression rescued the ciliogenesis defects and PKD phenotypes in Inpp5e‐depleted embryos. Taken together, our results reveal that apical PtdIns(4, 5)P2 is essential for ciliogenesis and the prevention of PKD and suggest a novel possibility for treating PKD and other human ciliopathies.—Xu, W., Jin, M., Huang, W., Wang, H., Hu, R., Li, J., Cao, Y. Apical PtdIns(4, 5)P2 is required for ciliogenesis and suppression of polycystic kidney disease. FASEB J. 33, 2848–2857 (2019). www.fasebj.org